If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 15q + -8 = 14 + 12q Reorder the terms: -14 + -8 + 15q = 14 + 12q Combine like terms: -14 + -8 = -22 -22 + 15q = 14 + 12q Solving -22 + 15q = 14 + 12q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-12q' to each side of the equation. -22 + 15q + -12q = 14 + 12q + -12q Combine like terms: 15q + -12q = 3q -22 + 3q = 14 + 12q + -12q Combine like terms: 12q + -12q = 0 -22 + 3q = 14 + 0 -22 + 3q = 14 Add '22' to each side of the equation. -22 + 22 + 3q = 14 + 22 Combine like terms: -22 + 22 = 0 0 + 3q = 14 + 22 3q = 14 + 22 Combine like terms: 14 + 22 = 36 3q = 36 Divide each side by '3'. q = 12 Simplifying q = 12
| 2n-6n= | | 156/28 | | 5y+6x+25=0 | | 16/8*2 | | 2(n+3)=15 | | 15/21-2/7 | | (2x+1)/5=(4x+7)/3 | | 2(3)=a | | y=-.908x+73.00 | | 2-3/6 | | -20r+13=-19r-3r-9 | | 8a-15=21-7a | | 2y+17=17 | | 2x^2-5/3x^2-27 | | z/42-69=70 | | 20+s=-15+14-2s | | f(x)=x/(7x-5) | | -26z-0.5=-36z+1.6 | | 2(1)+7=3 | | A=(61)(3) | | 8(x-8)+12=5x | | 3g+2(-6+3g)=1-6 | | 1-7(-2m-3)=8m+1 | | 4x+1-6.2x+2=0 | | 3p+6p+p=81+p | | 7f-16f-16=-6f+17 | | -16+20y=-4y+17+15 | | 3b-2b=-3 | | 5/3•11/3 | | 1.3x-0.02=1.9x+0.16 | | 12r-8-12(r+2)= | | 4x+10=4x-8 |